Aspectos anatômicos da cloaca de testudines - Rosa, Marcelo de Alcântara (2008)
This work investigate the disposal of openings ureters, urethra, oviducts of the female, and of the deferens ducts in the males, and the arrangement of the cloaca compartment in some species of the Podocnemididae and Chelidae family. The anatomic cloaca s study has three compartments: copordeum, urodeum and proctodeum. The cloaca has one urinary bladder and two cloacal bladders. In the studies species of genus Podocnemis and Geochelone genus there is a fold that separates coprodeum from urodeum. This fold isn t exists in the Chelidae family, used in this work. In P. expansa, P. unifilis and Chelus fimbriatus, urethra inserts cranioventrally in urodeum, but in Phynops geoffroanus, urethra is connecting with urodeum in vertical and ventral position. In the males of Podocnemis, the deferens ducts arrive caudally by a wall papilla and to the ureters openings. In the males of P. geoffroanus and C. fimbriatus and Podochemis female the oviducts and ureters confide in one urogenital sinus. In the females of P. geoffroanus and of C. fimbriatus, during the period of rounted-contourns reproductions training, the oviducts are projected to the urodeum and form a pair of papilla; each papilla possess a ventral opening. The proctodeum have a ventral fissure to communicate itself with urodeu. The opening of the coprodeu in the proctodeu, except in Chelidae, is an ofirice in fold s ventral parts that separate the two compartments.